Anticancer Activity of Typhonium flagelliforme: A Systematic Review - Crystalia, Audrey Amira; Hillary, Hillary (Indonesia International Institute for Life Sciences, 2022)
Cancer is a global health issues that can affect anyone. Cancer is treated conventionally with surgery, chemotherapy, radiotherapy, and hormone therapy. However, the high cost of conventional treatments is a burden for cancer patients. Therefore, many cancer patients seek for cheaper yet effective alternative treatments. Typhonium flagelliforme is a taro-like plant that can be found across Indonesia. Numerous researches on the anticancer effect of T. flagelliformehave been conducted. However, a systematic review on the anticancer property of T. flagelliforme is still lacking. Therefore, this review aimed to systematically evaluate the scientific evidence for the anticancer activities in T. flagelliforme. Five databases were used as the search engine using the designated search terms and studies were selected based on the inclusion criteria. The anticancer evaluation in 30 studies selected were conducted in leukemia, lymphoma, breast, oral, cervical, lung, liver, colon, and squamous cell carcinoma. The result showed that T. flagelliforme could inhibit cancer cell proliferation with most of the IC50 are less than 200 μg/mL. T. flagelliformeinduced an increase of caspase-3 and -9, as well as a decrease of the anti-apoptotic Bcl-2 protein expression. The expression of p21 protein was increased after treatment of T. flagelliforme extract while the tyrosine kinase, Ki67, HER2/neu, telomerase, and COX-2 expressions were decreased implying T. flagelliforme could inhibit tumor growth and development. Lastly, T. flagelliforme is also capable in reducing the possibility of cancer cell invasion. Findings suggest that T. flagelliforme is potential to further developed for cancer treatment.